Improvement of Learner Retention for English Online Courses in Center of Foreign Languages, Vietnam - Luu Nguyen Quoc Hung (Current Research in Language, Literature and Education Vol. 6, 2022)
Due to the closure of many schools as a result of the Covid-19 outbreak, online learning has exploded in popularity recently. While the number of online students is continually increasing, keeping them in online courses and programs has proven difficult. Retention rates are important indicators of an institution’s capacity to keep students engaged in their studies, meet their educational goals, and avoid dropping out. This study investigates 164 online learners at a center of foreign languages through an online survey with the goal of exploring various reasons why learners drop out of their online learning and identifying effective approaches to improve learner retention. The findings indicate that online learning is still a revolutionary trend of education and learner retention rates have been positive in most online courses. Common reasons for class attrition were figured out in the study, including busy work or school schedule, health problems, Internet or electricity supply problems and lack of appropriate interaction in online classes. Practical recommendations are provided so that institutions can quickly apply the findings to their policies and practices.